Improving Student’s Reading Comprehension on Narrative Text Through Directed Reading Think Pair Share (TPS) at Madrasa Aliyah - Nikmah, Alfi (Institut Agama Islam Negeri Kudus, 2020)
The purpose of the research was to find out the improvement of student’s reading comprehension on narrative text through directed reading and think pair share at madrasa Aliyah of Manahijul Huda Ngagel in academic years 2019/2020. This research was done by applying Classroom Action Research which carried out through four steps. They were planning, action, observation, and reflection, in cycle 1 and cycle 2. The subject of research was the grade X-MIA, they are consisted of 30 students. Based on the result of the data analysis showed that mean of the score has increased in the cycle 2, the mean in the pre-test was 63,33%, the mean of cycle 1 was 74,33%. Then the mean of cycle 2 was 84,17%. The students who got up 75 also grew up. In the pre-test, students who got up 75 were only 5 of 30 students (16,67%). In the post test of cycle 1, students who got up 75 were only 17 of 30 students (56,67%). It means that there was improvement about 40%. In the post test of cycle 2, students who got up 75 were 24 of 30 students (80%). The improvement was about 23,33%. The total improvement of the student’s score from the pre-test to post test of cycle 2 was 63,33%. So, the result of the research showed that Directed-reading and Think Pair Share (TPS) strategy significantly improved student’s reading comprehension on narrative text.